Involvement of P-gp on Reversing Multidrug Resistance Effects of 23-Hydroxybetulinic Acid on Chemotherapeutic Agents - Liu, Zhihao; Wen, Xiaozhou; Wang, Guangji; Zhou, Ying (Frontiers in Pharmacology, 2021)
Betulinic acid (BA) and 23-Hydroxybetulinic acid (23-HBA) are natural products with similar structures, which show a range of biological effects including antitumor activity. The purpose of this study was to evaluate and compare the combinational antitumor effects of BA and 23-HBA with chemotherapeutic agents in vitro, and to clarify the potential interaction and related mechanism with P-gp. 23-HBA, instead of BA, could increase sensitivity of MCF-7/ADR cells to adriamaycin (ADR) and vincristine (VCR). The intracellular accumulation of ADR/VCR in MCF-7/ADR cells was obviously increased in the presence of 23-HBA. Furthermore, 23-HBA could show dose-dependent increase on the transport of VCR and digoxin, which are both P-gp substrates, in both Caco-2 and MDCK-MDR1 cells. However, the transport of BA and 23-HBA was not influenced by the inhibition of P-gp in MDCK-MDR1 cells. MDR1 shift assay and molecular docking model suggested that both compounds are weak substrates of P-gp, yet, the binding affinity and sites are different. In conclusion, 23-HBA could significantly enhance the efficacy of chemotherapeutic agents in multidrug resistance (MDR) cells, which was related to the inhibition of P-gp. The in vitro and in silico study further revealed that 23-HBA and BA showed different interaction mechanism with P-gp.